2009
DOI: 10.1007/s11199-009-9587-7
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Fat Talk Among American Adults: Results from the Psychology of Size Survey

Abstract: Vignettes were used to assess gender differences in likelihood of hearing others engage in and perceived pressure to join in positive, negative (fat talk), and self-accepting body talk. An agerepresentative sample of 4,014 adult women and men voluntarily responded to an emailed "Health and Wellness" survey from an internet polling company with whom they had preregistered. Women reported more likelihood of hearing fat-talk scenarios and greater pressure to participate in them compared to men. Only a subset of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 15 publications
5
45
1
4
Order By: Relevance
“…Research indicates that women feel pressured to engage in fat talk, and that men also report being exposed to and participating in conversations about weight and appearance (Martz, Petroff, Curtin, & Bazzini, 2009). The majority of such talk is negative, focusing particularly on ways in which one's body fails to live up to one's own desires or societal expectations (Britton, Martz, Bazzini, Curtin, & LeaShomb, 2006).…”
Section: Fat Talk: Manifesting An Idealized Body Imagementioning
confidence: 99%
“…Research indicates that women feel pressured to engage in fat talk, and that men also report being exposed to and participating in conversations about weight and appearance (Martz, Petroff, Curtin, & Bazzini, 2009). The majority of such talk is negative, focusing particularly on ways in which one's body fails to live up to one's own desires or societal expectations (Britton, Martz, Bazzini, Curtin, & LeaShomb, 2006).…”
Section: Fat Talk: Manifesting An Idealized Body Imagementioning
confidence: 99%
“…[17] Bir başka çalışmada ise kilolu kadınların zayıf ve normal kilolu kadınlardan daha fazla kilo konuşmaları yapma eğiliminde oldukları saptanmıştır; bu sonuç kilolu ve obez olan kadınların daha çok kilo konuşması yapması, beden kaygılarının olması ve beden karşılaştırması yapması yönündeki hipotezimizle uyumludur. [18] Obezite sosyal, ekonomik ve psikolojik faktör-ler ile ilişkili olmasına rağmen bu ilişkilerin doğası tam olarak anlaşılmış değildir. [19] Literatürde, birçok çalışma depresyon ve obezitenin birlikteliğini göster-mektedir.…”
Section: Bulgularunclassified
“…[7] Yetişkin erkek ve kadın katılımcılarla birlikte yapılan bir çalışmada (yaş ortalaması=45) yaş ve kilo konuşması arasında düşük, negatif yönde bir ilişki bulunmuştur. [18] Bu araştırmada yaş (yaş ortancası = 27) ile kilo konuşmaları arasında bir ilişki bulunmamıştır. Ayrıca araştırma, daha genç bir popü-lasyonu temsil etmektedir.…”
Section: Bulgularunclassified
See 1 more Smart Citation
“…While researchers have begun to study the occurrence of fat talk among men, women seem to be more frequently exposed to fat talk and feel pressured to engage in fat talk in their social relationships (Martz, Petroff, Curtin, & Bazzini, 2009;Payne, Martz, Tompkins, Petroff, & Farrow, 2011). In a cross-sectional longitudinal study, Tzoneva, Forney, and Keel (2015) found that women in their 20s were more likely to be exposed to fat talk than women in their 30s and 40s and than men.…”
Section: Fat Talkmentioning
confidence: 99%